KONGRUENSI KARIR REMAJA-ORANG TUA DENGAN KOPING STRES PADA MAHASISWA TAHUN PERTAMA DAN KEDUA DI PROGRAM D3 KEPERAWATAN POLTEKKES KEMENKES SEMARANG - TALITHA AMANDA ULIMAZ (Jurnal EMPATI, 2017)
The first and second year students are in the moment where they have to strive to achieve the emotional independence and preparing their economic career. The existence of the demands and responsibilities of students in D3 Program make them to be clever enough to do coping stress. This study aims to determine the relationship between adolescent-parent  career congruence with coping stress in the first and second year students on D3 Nursing’s program Poltekkes Kemenkes Semarang. The population of this research is the first and second year students at D3 Nursing Program Poltekkes Kemenkes Semarang which amounted to 186. The research sample is 92 students (91.3% female subject, M age = 19.05 years, SD age = .63) obtained by cluster random sampling. Data collection using Coping Stress Scale (30 items, α = .91) and The Adolescent-Parent Career Congruence Scale (12 items, α = .90) were piloted on 44 students. The simple regression analysis shows that there is a significant positive relationship between adolescent parent-career congruence and coping stress (as shown by rxy value = .39 (p <.001). It means that if the adolescent-parent career congruence becomes higher, so the coping stress will be better. The adolescent-parent career congruence provides an effective contribution of 15.5% in coping stress.